Bird and Line: Tracing Indian Aesthetics to Find an Ecosophy of Personal Art Practice - Kalyanasundaram, Srisrividhiya (The Trumpeter)

(untitled) (Athabasca University Press, 2020)
"Bird and Line" is an artistic inquiry into the relationship between a deep state of artistic consciousness and the act of drawing a line to arrive at the form of a bird. This inquiry further proposes that by using line as a mode of research, the artist begins to perceive the consciousness of a bird and the relationship it shares with its form.For me, the embodied and porous experiences of watching and knowing birds through the practice of working with "line" as an artistic element allow for an intimacy of experiencing and an unfolding of intersubjectivity. Artistic inquiry also acts as an investigation into self-awareness and self-realization in this space of making eco-art. These acts of being lead me into reflections on how perception and creativity are melded together during creative moments to allow for a porous consciousness to emerge and perform the act of drawing a bird. As an artist working with text, movement, and image, I embed questions on the ethics of creativity into how we evolve our lines of art, as well as encounter other beings. By unraveling the relationship between the inner and the outer through Indian aesthetic philosophy, I evolve methods for eco-art practice using line as an element. I emphasize the importance of artistic research with a framework of Indian aesthetics as a way of deepening our perception and relationships with the natural world.This article is written to make artistic processes visible through a reflective auto-ethnographic approach. I write in a non-linear reflective narrative to comprehend cultural ontologies that drive my practice, unfolding internal thought processes, directions of research, and moments of mystical experience.